Tackling energy, climate and development challenges in Africa - Shingirirai S. Mutanga; Rainer Quitzow; Jan Christoph Steckel (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In order to fulfill multiple sustainable development targets, most prominently human development, poverty eradication and climate change mitigation, African countries need infrastructure that cover basic needs while at the same time promote industrialization and value creation. G20 countries can support African countries by: (1) aligning and cementing the G20 Agenda for Africa with African initiatives, SDGs and the Paris Agreement, (2) mitigating economic risks of climate change through supporting low carbon development pathways in Africa, (3) incentivizing low carbon development by phasing out subsidies and eventually putting a price on carbon and (4) creating and enabling a level playing field for low carbon technologies, which includes integrated strategies for de-risking renewable energy investments.
Keywords: Q01; Q54; H23; R11; 330; Sustainable development; climate policy; Africa